Social and Ethnic Transformation of Large Social Housing Estates in Milan, Italy: From Modernity to Marginalisation. - Petsimeris, Petros (Springer Open, 2018)
The chapter examines the case of large estates of social housing in Italy s economic capital, Milan. Production of this housing occurred in the period of intensive industrialisation and associated urbanisation from the late 1940s to the mid-1970s. Development of these schemes occurred mainly in the periphery of the city, and led to land speculation and changed the social geography of the city. These estates initially housed Italian economic migrants attracted to Milan during the economic miracle , and since the 1990s have been the residence of a growing number of international migrants. Housing estates ceased to be developed after the 1980s, and a large part of the stock has been privatised since the 1990s. Today housing estates are more heterogeneous in terms of tenancy regimes and the social and ethnic groups who live there. The majority of the stock shows signs of (often serious) physical deterioration. The resident population has aged in situ, with ethnic segregation occurring in some residual parts of the stock. This chapter studies the evolution of these large social housing estates in spatial and social terms, using published and unpublished data from 1951 to 2017, pointing out their critical points and their potential.
Keywords: Wohnungswesen; Sozialwohnung; Sozialer Wohnungsbau; Migration